Steroid Flare Reaction; a Complication of Intraarticular Steroid Injection - Haque, Anwar Ul; Haque, Anwar Ul (International Journal of Pathology, 2018)
A 63 year old man with bilateral knee osteoarthritis underwent an intraarticular steroid injection. After two daysthe patient developed severe pain and marked effusion in the left knee joint. Cultures were negative. He subsequentlyunderwent bilateral knee replacement. The synovial biopsy of the left knee revealed marked granulationtissue and peculiar neutrophilic response against degenerated cartilage and osseous tissue.